2011
DOI: 10.4103/0019-5049.79883
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and clonidine in epidural anaesthesia: A comparative evaluation

Abstract: Efforts to find a better adjuvant in regional anaesthesia are underway since long. Aims and objectives are to compare the efficacy and clinical profile of two α-2 adrenergic agonists, dexmedetomidine and clonidine, in epidural anaesthesia with special emphasis on their sedative properties and an ability to provide smooth intra-operative and post-operative analgesia. A prospective randomized study was carried out which included 50 adult female patients between the ages of 44 and 65 years of (American Society of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
253
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(296 citation statements)
references
References 33 publications
35
253
5
3
Order By: Relevance
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Our data support previous studies that used dexmedetomidine and clonidine as additive to regional anesthetics. [5], [26], [27] We found no statistical significance in the peak levels of analgesia provided by both drugs. Our findings were in concordance with Salgado etal.…”
Section: Discussionmentioning
confidence: 90%
“…The prolongation of the motor block of local anesthetics may be the result of binding of α-2 adrenoreceptor agonists to the motor neurons in the dorsal horn. [4], [5] Dexmedetomidine is eight times more specific and highly selective α-2 adrenoreceptor agonist compared to clonidine. [20], [25] This study was undertaken to compare the analgesic efficacy, and sedative effects of two α-2 agonists when administered epidurally along with bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations